Prediction of rheological behavior of a new hybrid nanofluid consists of copper oxide and multi wall carbon nanotubes suspended in a mixture of water and ethylene glycol using curve-fitting on experimental data - Tian, Zhe; Rostami, Sara; Taherialekouhi, Roozbeh; Karimipour, Arash; Moradikazerouni, Alireza; Yarmand, Hooman; Zulkifli, Nurin Wahidah Mohd (Elsevier, 2020)
In the current study incorporating nanoparticles of CuO/MWCNTs into the base fluid water/EG (70:30) has been done to investigate the nanofluid rheological behavior in the temperature of 20–60 °C. Employing two-step method, homogeneous and stable samples of nanofluid at various nanoparticles volume fractions (0.025, 0.05, 0.1, 0.25, 0.5 and 1%) have been prepared. Based on the experiment results, base fluid (water/EG (70:30)) is treated as a fluid with Newtonian behavior. Incorporating nanoparticles at volume fractions of 0.025, 0.05, 0.1 and 0.25 has no effects on Newtonian behavior of the base fluid, while in the volume fractions of 0.5 and 1% changes the behavior from Newtonian to non-Newtonian. For Newtonian behavior, adding nanofluid led to increase in viscosity up to 95.67%. It was found that sensitivity of the viscosity to the volume fraction at low temperatures is more, while less viscosity sensitivity to the temperature at low volume fractions. © 2020 Elsevier B.V.